2019
DOI: 10.1002/jcp.28998
|View full text |Cite
|
Sign up to set email alerts
|

Hippuric acid and 3‐(3‐hydroxyphenyl) propionic acid inhibit murine osteoclastogenesis through RANKL‐RANK independent pathway

Abstract: Nutritional factors influence bone development. Previous studies demonstrated that bone mass significantly increased with suppressed bone resorption in early life of rats fed with AIN‐93G semi‐purified diets supplemented with 10% whole blueberry (BB) powder for 2 weeks. However, the effects of increased phenolic acids in animal serum due to this diet on bone and bone resorption were unclear. This in vitro and in ex vivo study examined the effects of phenolic hippuric acid (HA) and 3‐(3‐hydroxyphenyl) propionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…We treated RAW 264.7 cells under osteoclast differentiation condition with serum collected from LLC-bearing mice and tumor-free control mice. ( Figure 3 g) [ 49 ]. We then determined the expression level of nuclear factor-activated T cells c1 (NFATc1), a master regulator of osteoclast differentiation [ 50 ], and cathepsin K (CTSK), a phenotypic marker of osteoclast [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…We treated RAW 264.7 cells under osteoclast differentiation condition with serum collected from LLC-bearing mice and tumor-free control mice. ( Figure 3 g) [ 49 ]. We then determined the expression level of nuclear factor-activated T cells c1 (NFATc1), a master regulator of osteoclast differentiation [ 50 ], and cathepsin K (CTSK), a phenotypic marker of osteoclast [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported an in vitro study suggested that HA and 3-3-PPA inhibit osteoclastogenesis and bone resorption through suppressing GPR109A in pre-osteoclasts 15 . To further search possible membrane GPR109A-mediated actions of HA and 3-3-PPA on inhibition of osteoclastogenesis, we performed an in ex vivo study.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the apparent interactions of diet-derived phenolics and GPR109A on osteoclast function in cell models 15 , we fed BB and HA supplemented diets to male wild type and GPR109A −/− mice for 40 days. Micro-CT determined that bone volume per total tissue volume and trabecular number were significantly higher in GPR109A −/− mice compared with age-matched wild type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another half of the hematopoietic nonadherent bone marrow cells were cultured in 96‐well plates (2 × 10 4 cells/well) in the presence of 30 ng/ml of RANKL. As we described previously, ( 37 ) after 5 days for nonadherent bone marrow cell cultures, the cells were fixed with 4% paraformaldehyde and stained for TRAPase activity using a TRAPase staining kit according to the manufacturer's protocols (acid phosphatase leukocyte, procedure No. 386; Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%